WATER STRESS ON DIFFERENT GROWING STAGES FOR QUINOA (Chenopodium quinoa willd) AND ITS INFLEUNCE ON WATER REQUIRIMENTS AND YIELD - & et al., Salim (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
A factorial experiment was conducted within split-split plot design with three replicates. Four genotypes seeds (Regalona, Q-37, KVL-SR2, and Q21) were planted in the sub plots while six water treatments distributed in the main plots. They were ordinary river irrigation (S0), stress at emergence (S1), branching (S2), at ear formation (S3), at flowering (S4), and at maturity (S5). Irrigation water was applied in the normal irrigation when 50-60% of the available water was depleted and one irrigation was omitted from the water stress treatments. Reference and actual evapotranspiration, pan evaporation, yield, crop coefficient, and water use efficiency were calculated. Mean irrigation requirement for the four genotypes based on irrigation scheduling was 230.8 mm, decreased by 14 and 17% under stress conditions of the drought tolerant stages. Grain yield ranged between 3.1 and 5 Mg ha-1 for water stress treatments compared to 5.6 and 4.2 mg. ha-1 for normal irrigation treatments. Genotype Q21 gave the highest yield and differed significantly from others. Field water use efficiency ranged between 1.6 to 1.1 kg m-3 and crop water use efficiency 1.38 to 2.22 kg m-3. KVL-SR2 and Q21 showed the highest efficiency (1.87 kg m-3). Results indicated that the stage of ear formation and flowering are the most tolerant to water stress. On the other hand, the branching, and maturity were critical stages with high reduction in yield under stress conditions.